2022
DOI: 10.1111/bjso.12605
|View full text |Cite
|
Sign up to set email alerts
|

No borders on a fragile planet: Introducing four lay models of social psychological precarity to support global human identification and citizenship

Abstract: No borders on a fragile planet: Introducing four lay models of social psychological precarity to support global human identification and citizenship. British Journal of Social Psychology (Early access).For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Lower SES individuals in societies such as the United States seem capable of utilizing TSD resources to cope with financial threats, even at the potential cost of worse mental health. However, our findings may not generalize outside of the US or other “WEIRD” populations (Henrich et al, 2010), such as contexts of comparatively low access to TSD affordances and forms of precarity in the Global South and elsewhere that centre around hierarchical geopolitical relations such as coloniality or the use of borders to control migration (Mahendran, et al, 2022; Hakim, et al, 2022).…”
Section: Discussionmentioning
confidence: 78%
“…Lower SES individuals in societies such as the United States seem capable of utilizing TSD resources to cope with financial threats, even at the potential cost of worse mental health. However, our findings may not generalize outside of the US or other “WEIRD” populations (Henrich et al, 2010), such as contexts of comparatively low access to TSD affordances and forms of precarity in the Global South and elsewhere that centre around hierarchical geopolitical relations such as coloniality or the use of borders to control migration (Mahendran, et al, 2022; Hakim, et al, 2022).…”
Section: Discussionmentioning
confidence: 78%
“…The dynamics of self-other/-world relations in becomings of precarity Whilst subjectivities and affective dimensions are linked to the processual nature of precarity in social science theorizing, papers in this special issue explore the dynamics of these processes in depth. Adam-Troian et al (2022) and Mahendran et al (2022) draw attention to the ways in which (different formulations of) precarity, experienced as 'threat', shape societal relations and political decision-making. Mahendran and colleagues (2022) further expand this view of societal relations through their use of the migration-mobility continuum (which locates all humans on a scale of migration) in exploring the differ-ent ways in which people make sense of, and might seek to change, our bordered world.…”
Section: Looking Outmentioning
confidence: 99%
“…The final two contributions to the special issue speak to this methodological call for exploring precarity as something that is experienced by all. In Mahendran et al ( 2022 ), different models or manifestations of ‘psychological precarity’, identified as the sense of threat and insecurity that is inherent to people's identifications with ‘the global’, is explored through the development of an innovative methodology. Participants are given the ‘hyperagentic’ position of choosing how or if to construct borders on maps of the world, generating insight into the different relationalities (with both human others and more‐than‐human worlds) which constitute everyday understandings of precarity.…”
Section: Contributions To This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…These writers examine if and how, a high TSD, as an aspect of 'modern capitalism' widens disparities, reduces flexibility, imposes disadvantage and layers on substantial stressors for poor and working-class people, while parading as 'flexibility' and 'choice'. Mahendran et al 2022, with interdisciplinary theorizing and stunningly creative methodologies, situate subjectivities within an even more expansive field of global dynamics where precarity and migration intersect with agency and desire. They explore global and planetary consciousness with two interactive methods-the IWAH (identification with all humanity) global identification scale and the IWMT (international worldview mapping tool).…”
Section: Suturing Personal Subjectivities and The Materials World: Ec...mentioning
confidence: 99%